Basal Cell Adenoma of the Parotid Gland - Amalanathan, S.; Kumar, C. S.; Sinhasan, S. P. (Kathmandu University Medical Journal, 2020)
Basal Cell Adenoma (BCA) known as monomorphic adenoma is a rare type of benign epithelial salivary neoplasm that mostly occurs in the parotid gland. Clinically BCA appears as a firm, mobile, slow-growing mass and is usually diagnosed during the histopathological examination of the resected surgical specimen. Histological differential diagnosis ranges from benign to malignant neoplasms such as pleomorphic adenoma, basal cell adenocarcinoma, adenoid cystic carcinoma and basaloid squamous cell carcinoma. The treatment of BCA is surgical excision, due to its varied prognosis with the different histological subtypes; a regular long term follow up of the patient postoperatively is mandatory. We report a rare and interesting case of basal cell adenoma of the parotid gland in a 52 year old female. We review the literature; discuss the diagnosis and management of this rare histological entity.